The Effectiveness of Using Flashcard to Improve the Vocabulary Mastery of Eight Grade Students at SMPN 38 Palembang - Nanda Shenja Lestari; Nike Angraini; Jaya Nur Iman (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
Mastering Vocabulary played a pivotal role in learning English, as it comprised a collection of words that, when used, construct meaningful sentences. Consequently, the more words a student masters, the more effortlessly they could construct sentences and effectively communicate their thoughts. The purpose of the study was to determine the level of use of flashcards in improving student vocabulary and to find out the use of flashcards can provide a significant difference in the mastery of vocabulary of students who use flashcards and those who do not use flashcards among 8th grade students of SMP 38 Palembang. The quantitative technique was used for this study research. The sample of this research VIII.5 and VIII.6 class, each class consisted of 34 students, with a total sample of 68 students. Additionally, the result of an independent sample t-test revealed that at a significance level of 0,05, t-obtained was 6,320 > t-table (df=66) was 1,997. It denoted that experimental and control group means significantly differed. After having the results of the t-test it can be concluded that team- assisted individualization was useful and applicable for enhancing students’ mastery of English vocabulary among eighth-grade students at SMP Negeri 38 Palembang.